Analysis of the Implications of the Indonesian Criminal System with the Problems of Correctional Institution Conditions (Research Study at Class IIB Pati Prison) - Prihartadi, Prihartadi; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
In a prisoner during his/her imprisonment, the attitudes and values adopted by a prisoner in the context of the prisoner's society will seriously hinder the prisoner's resocialization efforts. This is also the obligation of policy makers or related employees in handling this prison overcapacity case because it is feared that it will hinder the prisoner development process and hinder the suppression of crime rates in the future. The aim of this research is to determine and analyze (1) the dynamics of the Indonesian criminal justice system from a legal construction perspective, (2) the implications of the problems of the Indonesian criminal justice system with the current conditions of correctional institutions, (3) the concept of an ideal criminal justice system in overcoming the problems of correctional institutions. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. While secondary data is obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research and discussion, it can be concluded: (1) The criminal punishment system in the Criminal Code, where the Indonesian Criminal System is basically regulated in Book I of the Criminal Code in Chapter 2 from Article 10 to Article 43. The criminal system in the Criminal Code is divided into 2 types of sanctions, namely first, the main punishment consisting of the death penalty, imprisonment, confinement, fines and imprisonment; second, additional punishment. (2) Criminal law policy in Indonesia shows over-criminalization and over-use of imprisonment. This can be seen from the formulation of criminal law in the Criminal Code and the development of criminal law formulations outside the Criminal Code. Article 10 of the Criminal Code stipulates the types of main punishments, namely the death penalty; imprisonment; confinement, confinement and fines. (3) When looking at the renewal of correctional policies to improve the worsening situation and conditions of Indonesian Correctional Institutions with the enactment of Law Number 22 of 2022 concerning Corrections, which has the right direction, ideas and philosophy for the conditions that have occurred, there are aspects that are upheld in the restorative justice paradigm.